Multi-purpose low-cost lithium battery electrode material section preparation method

Through argon ion beam polishing technology, the lithium battery electrode material is roughly processed in the ion thinning instrument, which solves the problems of poor cross-sectional flatness, long time and high cost of electrode material, and achieves efficient and low-cost cross-sectional preparation of electrode material , meet the needs of diversified observations.

CN119309890APending Publication Date: 2025-01-14EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411448462.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing lithium battery electrode material cross-sectional preparation methods have problems such as poor flatness, long time, high cost and inability to meet the needs of diversified surface preparation.

Method used

The electrode material of lithium battery is roughed and finished in an ion thinner meter by using argon ion beam polishing technology. The electrode material cross-section is realized through high voltage roughing and low voltage finishing, combined with the fixing method of conductive copper sheet and current collector. leveling preparation.

Benefits of technology

It significantly improves the flatness and processing efficiency of the cross-section of the lithium battery electrode material, reduces costs, meets the sample preparation needs of in-situ and off-situ observations, provides clear internal structure observations, and is suitable for diversified electrode material failure research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119309890A_ABST
    Figure CN119309890A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a multipurpose low-cost lithium battery electrode material section, and belongs to the technical field of new energy battery material characterization. According to the invention, different fixing modes are developed in consideration of different requirements of the cross section of the lithium battery electrode material for off-site characterization and in-situ observation; the method can meet the requirement for section observation of diversified lithium battery electrode materials, operation is easy, the machining success rate is high, and the machining cost is reduced. Experimental results show that the section of the lithium battery electrode material prepared by the preparation method of the section of the lithium battery electrode material is flat and smooth, and cracks and morphology in particles are clear and visible; the processed sample can be directly used for shooting a high-quality scanning electron microscope image and performing energy spectrum analysis, so that further statistics and analysis on the failure form of the electrode material by utilizing artificial intelligence algorithms such as machine learning are facilitated; and in addition, the device can be assembled into a battery in-situ observation device for electrode material cycle test and structure real-time evolution observation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy battery material characterization, and in particular relates to a multi-purpose and low-cost lithium battery electrode material cross-section preparation method. Background Art

[0002] Currently, lithium batteries are widely used in aerospace, transportation, energy storage, and mobile communications. These application scenarios have put forward higher requirements on the energy density, cycle life, and cost of batteries. Positive and negative electrode materials are key factors in determining the performance of lithium batteries. During the lithium battery cycle charge and discharge test, the positive and negative electrode materials will expand and shrink in volume as lithium ions are extracted and embedded. Under long-term cycle conditions, cracks will appear in the electrode material particles due to frequent volume expansion and contraction, which will cause the instability of the material structure and aggravate the side reactions at the interface, thus affecting the battery life. Therefore, it is urgent to explore the internal structural evolution mechanism of positive and negative electrode material particles to provide guidance for improving the performance and structural optimization synthesis of positive and negative electrode materials. Using characterization methods such as scanning electron microscopy or optical microscopy to achieve ex-situ characterization or in-situ observation of the internal structural evolution and composition changes of positive and negative electrode material particles requires obtaining a flat cross-section of the electrode material particle sample.

[0003] The methods for processing electrode material cross sections mainly include metallographic grinding and polishing, CP (ion milling) and FIB (focused ion beam). Among them, metallographic grinding and polishing uses cold mounting or hot mounting resin material coating. The processing technology is relatively complicated and the sample preparation effect is easily affected by factors such as processing temperature, grinding and polishing reagents and conductivity. The obtained sample cross section has poor flatness and takes a long time; CP (ion milling) is the mainstream method for the current preparation of electrode material cross sections, which can achieve a large range of electrode material cross section processing, but the processing cost is high; FIB (focused ion beam) is suitable for the preparation of small area samples of single or several particles, and at the same time, it is limited by processing time and expensive costs, and cannot be applied to the preparation of electrode material cross sections in larger areas. In summary, the use of argon ion beam to prepare electrode material cross sections can obtain a more ideal electrode material particle cross section, but it is limited by factors such as processing cost and preparation time. Consider how to give full play to the functions of other existing argon ion beam processing equipment to reduce preparation time and cost. In addition, the current electrode material cross section sample preparation method is mainly used for off-site characterization, which cannot meet the needs of cross section sample preparation for in-situ observation.

[0004] Therefore, in view of the current problems of uneven cross-section of electrode materials, long preparation time, high price and inability to meet the diverse surface preparation needs of electrode materials, a method for preparing cross-sections of electrode materials with diverse uses and low cost is needed to solve the above technical needs. Summary of the invention

[0005] The purpose of the present invention is to provide a multi-purpose and low-cost method for preparing cross-sections of lithium battery electrode materials. The method for preparing cross-sections of lithium battery electrode materials provided by the present invention can meet the requirements of preparing electrode sample materials for in-situ and ex-situ observations, and can provide good cross-section flatness of electrode materials. The present invention applies an ion thinning instrument to the preparation of cross-section samples of lithium battery electrode materials, expanding the application field of the device.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a multi-purpose and low-cost method for preparing a cross section of a lithium battery electrode material, comprising:

[0008] The current collector of the lithium battery electrode material is fixed on the conductive copper sheet, and then the active material of the lithium battery electrode material is polished by argon ion beam;

[0009] Alternatively: fixing the active material of the lithium battery electrode material on a conductive copper sheet, then performing argon ion beam polishing on the current collector of the lithium battery electrode material until the active material is exposed, and then performing argon ion beam polishing on the exposed active material;

[0010] Alternatively: coating the open-pore current collector with an active material to obtain a lithium battery electrode material;

[0011] Fixing the active material of the lithium battery electrode material on a conductive copper sheet, and then performing argon ion beam polishing on the active material at the opening of the current collector;

[0012] The argon ion beam polishing includes rough machining and fine machining performed sequentially;

[0013] The parameters of the rough machining include: machining time 20 to 30 min, voltage 6 to 10 kV and ion beam angle 3 to 10°;

[0014] The parameters of the finishing process include: processing time 30 to 90 min, voltage 3 to 6 kV and ion beam angle 3 to 10°;

[0015] The voltage for rough machining is higher than the voltage for fine machining.

[0016] Preferably, the lithium battery electrode material is a ternary polycrystalline positive electrode material, a ternary single crystal positive electrode material or a silicon-carbon negative electrode material.

[0017] Preferably, obtaining the lithium battery electrode material includes disassembling the battery.

[0018] Preferably, the types of batteries in the disassembled batteries include button batteries, cylindrical batteries or soft-pack batteries.

[0019] Preferably, the argon ion beam polishing is performed in an ion thinning instrument.

[0020] Preferably, the rotation speed of the lithium battery electrode material during the argon ion beam polishing is 3 r / min.

[0021] Preferably, the rough machining parameters include: machining time 20-30 min, voltage 8-10 kV and ion beam angle 3-8°.

[0022] Preferably, the parameters of the fine machining include: machining time of 60 to 90 min, voltage of 3 to 6 kV and ion beam angle of 3 to 4°.

[0023] Preferably, when the lithium battery electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) positive electrode material, the rough machining time is 30min, the voltage is 6kV, the ion beam angle is 3-4°, and the rotation speed is 3r / min; the fine machining time is 60-90min, the voltage is 3kV, the ion beam angle is 3-4°, and the rotation speed is 3r / min.

[0024] Preferably, when the lithium battery electrode material is a silicon-carbon negative electrode material, the processing time for the rough machining is 20 min, the voltage is 10 kV, the ion beam angle is 8°, and the rotation speed is 3 r / min; the processing time for the fine machining is 20 min, the voltage is 6 kV, the ion beam angle is 4°, and the rotation speed is 3 r / min.

[0025] The invention provides a multi-purpose and low-cost method for preparing a cross section of a lithium battery electrode material, comprising: fixing a current collector of the lithium battery electrode material on a conductive copper sheet, and then performing argon ion beam polishing on the active material of the lithium battery electrode material; or: fixing the active material of the lithium battery electrode material on a conductive copper sheet, and then performing argon ion beam polishing on the current collector of the lithium battery electrode material until the active material is exposed, and then performing argon ion beam polishing on the exposed active material; or: coating an open-pore current collector with an active material to obtain a lithium battery electrode material, fixing the active material of the lithium battery electrode material on a conductive copper sheet, and then performing argon ion beam polishing on the active material at the open hole of the current collector; the argon ion beam polishing comprises rough machining and fine machining performed in sequence; the parameters of the rough machining include: machining time of 20 to 30 minutes, voltage of 6 to 10 kV and ion beam angle of 3 to 10 degrees; the parameters of the fine machining include: machining time of 30 to 90 minutes, voltage of 3 to 6 kV and ion beam angle of 3 to 10 degrees; the voltage of the rough machining is higher than the voltage of the fine machining. When the cross section of the prepared lithium battery electrode material is used for ex-situ characterization, the present invention fixes the current collector of the lithium battery electrode material on a conductive copper sheet, and then performs argon ion beam polishing on the active material of the lithium battery electrode material; when the cross section of the lithium battery electrode material needs to be used for in-situ observation of battery assembly, the present invention fixes the active material of the lithium battery electrode material on a conductive copper sheet, and then performs argon ion beam polishing on the active material at the opening of the current collector, or fixes the active material of the lithium battery electrode material on a conductive copper sheet, and then performs argon ion beam polishing on the current collector of the lithium battery electrode material until the active material is exposed, and then performs argon ion beam polishing on the exposed active material. The above steps can meet the preparation of electrode sample materials for in-situ and ex-situ observations; the lithium battery electrode material is subjected to rough processing and fine processing in sequence by using argon ion beam polishing technology, and the rough processing is performed at high voltage, and the argon ion beam energy is relatively high, which can quickly cut the hard surface of the lithium battery electrode material to shorten the processing time, and then the fine processing is performed at low voltage to reduce polishing scratches, thereby improving the surface flatness. The experimental results show that the cross-section of the lithium battery electrode material prepared by the cross-section preparation method provided by the present invention is flat and smooth, and the cracks and morphology inside the particles are clearly visible, which is conducive to the subsequent scanning electron microscope analysis or in-situ optical microscope observation of the sample cross-section. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a structural schematic diagram of the cross-section preparation method of the lithium battery electrode material of the present invention; in the figure, 1 is the lithium battery electrode material, 2 is the conductive glue, 3 is the conductive copper sheet, 4 is the working range of the argon ion beam, and 5 is the sample processing rotation direction;

[0027] Figure 2 This is a cross-sectional SEM image of the lithium battery electrode material prepared in Example 1;

[0028] Figure 3 This is a cross-sectional SEM image of the lithium battery electrode material prepared in Example 2;

[0029] Figure 4 This is a cross-sectional SEM image of the lithium battery electrode material prepared in Example 3;

[0030] Figure 5 This is a cross-sectional SEM image of the lithium battery electrode material prepared in Comparative Example 1;

[0031] Figure 6 This is a cross-sectional SEM image of the lithium battery electrode material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0032] The present invention provides a multi-purpose and low-cost method for preparing a cross section of a lithium battery electrode material, comprising:

[0033] The current collector of the lithium battery electrode material is fixed on the conductive copper sheet, and then the active material of the lithium battery electrode material is polished by argon ion beam;

[0034] Alternatively: fixing the active material of the lithium battery electrode material on a conductive copper sheet, then performing argon ion beam polishing on the current collector of the lithium battery electrode material until the active material is exposed, and then performing argon ion beam polishing on the exposed active material;

[0035] Alternatively: coating the open-pore current collector with an active material to obtain a lithium battery electrode material;

[0036] Fixing the active material of the lithium battery electrode material on a conductive copper sheet, and then performing argon ion beam polishing on the active material at the opening of the current collector;

[0037] The argon ion beam polishing includes rough machining and fine machining performed sequentially;

[0038] The parameters of the rough machining include: machining time 20 to 30 min, voltage 6 to 10 kV and ion beam angle 3 to 10°;

[0039] The parameters of the finishing process include: processing time 30 to 90 min, voltage 3 to 6 kV and ion beam angle 3 to 10°;

[0040] The voltage for rough machining is higher than the voltage for fine machining.

[0041] In one technical solution of the present invention, the present invention fixes the current collector of the lithium battery electrode material on a conductive copper sheet, and then performs argon ion beam polishing on the active material of the lithium battery electrode material.

[0042] The present invention has no special limitation on the source of the lithium battery electrode material, and it can be prepared by using commercial products or well-known preparation methods known to those skilled in the art. In the present invention, the lithium battery electrode material is preferably composed of a stacked active material and a current collector.

[0043] In the present invention, the lithium battery electrode material is preferably a ternary polycrystalline positive electrode material, a ternary single crystal positive electrode material or a silicon-carbon negative electrode material.

[0044] In the present invention, obtaining the lithium battery electrode material preferably includes disassembling the battery; the type of battery in the disassembled battery preferably includes button batteries, cylindrical batteries or soft-pack batteries. The present invention has no special limitation on the source of the battery, and commercially available products known to those skilled in the art can be used.

[0045] In the present invention, the disassembly is preferably carried out in a glove box with an argon environment; the oxygen content of the glove box is preferably <0.1 ppm; and the humidity of the glove box is preferably <0.1 ppm.

[0046] In the present invention, the lithium battery electrode material is preferably cleaned, dried and cut in sequence before use.

[0047] The present invention has no special limitation on the cleaning operation, as long as the cleaning is complete.

[0048] The present invention has no special limitation on the drying operation, and the surface is dried after the cleaning solvent is completely evaporated.

[0049] In the present invention, the cutting is preferably performed by a knife or laser cutting. The present invention has no particular limitation on the size of the cutting, and the cutting can be performed according to the size of the required sample.

[0050] In the present invention, the fixing preferably uses conductive glue. The fixing using conductive glue in the present invention can ensure that the lithium battery electrode material will not move due to argon ion beam bombardment during the processing, while enhancing the conductivity.

[0051] In the present invention, the conductive adhesive is preferably a carbon conductive tape. The present invention has no special limitation on the source of the carbon conductive tape, and commercial products well known to those skilled in the art can be used.

[0052] In the present invention, the diameter of the conductive copper sheet is preferably 3 mm. The present invention has no special limitation on the source of the conductive copper sheet, and commercial products well known to those skilled in the art can be used.

[0053] In the present invention, the argon ion beam polishing includes rough machining and fine machining performed sequentially.

[0054] In the present invention, the parameters of the rough machining include: machining time 20-30 min, voltage 6-10 kV and ion beam angle 3-10°; preferably: machining time 20-30 min, voltage 8-10 kV and ion beam angle 3-8°, more preferably: machining time 25-30 min, voltage 9-10 kV and ion beam angle 6-8°. The present invention can further improve the flatness of the cross section of the lithium battery electrode material by limiting the parameters of the rough machining within the above range, and can also shorten the preparation time of the cross section of the lithium battery electrode material.

[0055] In the present invention, the parameters of the finishing process include: a processing time of 30 to 90 minutes, a voltage of 3 to 6 kV, and an ion beam angle of 3 to 10 degrees, preferably: a processing time of 60 to 90 minutes, a voltage of 3 to 6 kV, and an ion beam angle of 3 to 4 degrees. The present invention can further improve the flatness of the cross section of the lithium battery electrode material by limiting the parameters of the finishing process within the above range.

[0056] In the present invention, the voltage of the rough machining is higher than the voltage of the fine machining. The present invention adopts argon ion beam polishing technology to sequentially perform rough machining and fine machining on the lithium battery electrode material. The rough machining is performed at a high voltage, and the argon ion beam energy is relatively high, which can cut the hard surface of the lithium battery electrode material. Then, the fine machining is performed at a low voltage to reduce polishing scratches, thereby improving the surface flatness.

[0057] In the present invention, the argon ion beam polishing is preferably performed in an ion milling instrument; the model of the ion milling instrument is preferably Fischione Model 1051TEM Mill. The present invention uses an ion milling instrument for preparing cross-sectional samples of lithium battery electrode materials, expanding the application field of the equipment.

[0058] In the present invention, the ion thinning instrument preferably includes a single or multiple ion beam guns, and more preferably includes a dual ion beam gun. The dual ion beam gun can perform argon ion beam polishing on the surface of the lithium battery electrode material from both sides of the sample stage.

[0059] In the present invention, the rotation speed of the lithium battery electrode material during the argon ion beam polishing is preferably 3r / min. During the cross-section processing, the lithium battery electrode material of the present invention will rotate with the sample stage at a relatively low speed, enabling the argon ion beam to continuously cut the surface of the lithium battery electrode material, greatly reducing the processing marks of the ion beam and further improving the flatness of the cross section.

[0060] In the present invention, when the lithium battery electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O 2When the (NCM811) positive electrode material is used, the processing time of the rough machining is preferably 30 minutes, the voltage is preferably 6 kV, the ion beam angle is preferably 3-4 degrees, and the rotation speed is preferably 3 r / min; the processing time of the fine machining is preferably 60-90 minutes, the voltage is preferably 3 kV, the ion beam angle is preferably 3-4 degrees, and the rotation speed is preferably 3 r / min.

[0061] In the present invention, when the lithium battery electrode material is a silicon-carbon negative electrode material, the processing time of the rough machining is preferably 20 minutes, the voltage is preferably 10 kV, the ion beam angle is preferably 8°, and the rotation speed is preferably 3 r / min; the processing time of the fine machining is preferably 20 minutes, the voltage is preferably 6 kV, the ion beam angle is preferably 4°, and the rotation speed is preferably 3 r / min.

[0062] In another technical solution of the present invention, the present invention fixes the active material of the lithium battery electrode material on a conductive copper sheet, then performs argon ion beam polishing on the current collector of the lithium battery electrode material until the active material is exposed, and then performs argon ion beam polishing on the exposed active material.

[0063] In the present invention, the lithium battery electrode material is preferably the same as the aforementioned technical solution, which will not be described in detail here.

[0064] In the present invention, the fixing operation is preferably the same as the aforementioned technical solution, which will not be described in detail here.

[0065] In the present invention, the operation of the argon ion beam polishing is preferably the same as the aforementioned technical solution, which will not be described in detail herein.

[0066] In another technical solution of the present invention, the present invention coats an open-pore current collector with an active material to obtain a lithium battery electrode material; fixes the active material of the lithium battery electrode material on a conductive copper sheet, and then performs argon ion beam polishing on the active material at the opening of the current collector.

[0067] In the present invention, the aperture of the opening is preferably ≤0.3 mm. In the present invention, the opening is an observation window for subsequent observation of the cross section of the active material.

[0068] The present invention has no particular limitation on the operation of coating the active material on the open-pored current collector, and the operation well known to those skilled in the art may be adopted.

[0069] After coating the active material, the present invention preferably sequentially dries and cuts the product obtained by coating the active material to obtain a lithium battery electrode material.

[0070] The present invention has no particular limitation on the drying operation, as long as the surface is completely dried.

[0071] In the present invention, the cutting is preferably performed by a knife or laser cutting. The present invention has no special limitation on the size of the cutting, and the cutting is performed according to the required size of the sample, while ensuring that the opening position is located near the center of the circular pole piece.

[0072] In the present invention, the fixing operation is preferably the same as the aforementioned technical solution, which will not be described in detail here.

[0073] In the present invention, the edge of the active material of the lithium battery electrode material is preferably fixed on the conductive copper sheet. The present invention fixes the edge of the active material on the conductive copper sheet, which is conducive to preserving the complete electrode sample, thereby facilitating the subsequent removal of the conductive copper sheet, and further ensuring the performance of the electrode after the battery in-situ observation device is assembled.

[0074] The present invention has no special limitation on the size of the edge, which can be adjusted according to actual conditions.

[0075] In the present invention, the operation of the argon ion beam polishing is preferably the same as the aforementioned technical solution, which will not be described in detail herein.

[0076] The cross-section preparation method of the lithium battery electrode material provided by the present invention, combined with the sample structure and argon ion beam processing, can meet the diverse electrode material failure research, such as the cross-section preparation of the lithium battery electrode material observed in situ and the cross-section preparation of the electrode material after cycling; at the same time, the method is simple to operate, short in time, has a high success rate in sample processing, and significantly reduces costs. The cross-section processed by this method is flat and smooth without obvious processing traces remaining. The prepared samples can be directly used to take high-quality scanning electron microscope images and energy spectrum analysis, which helps to further count and analyze the failure forms of lithium battery electrode materials using artificial intelligence algorithms such as machine learning, and can also be assembled into a battery in-situ observation device for lithium battery electrode material cycle testing and observation.

[0077] The surface sample prepared by the lithium battery electrode material cross-section preparation method of the present invention can be directly photographed with a scanning electron microscope (SEM) image and subjected to energy spectrum analysis, without the need for additional treatment such as gold spraying or carbon spraying on the electrode sample; the lithium battery electrode material cross-section preparation method of the present invention can obtain a better lithium battery electrode material cross-section effect, avoiding damage to the internal morphology and structure of the electrode material due to the sample preparation process.

[0078] The structural schematic diagram of the cross-section preparation method of the lithium battery electrode material of the present invention is as follows Figure 1 As shown; in the figure, 1 is the lithium battery electrode material, 2 is the conductive glue, 3 is the conductive copper sheet, 4 is the working range of the argon ion beam, and 5 is the sample processing rotation direction.

[0079] from Figure 1 The processing principle of the cross section of the lithium battery electrode material of the present invention can be clearly understood.

[0080] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0081] Example 1

[0082] The cross-section preparation method of the lithium battery electrode material is as follows:

[0083] (1) disassembling the battery to obtain the ternary positive electrode material electrode piece, the disassembly process is carried out in a glove box with an argon environment, and the oxygen content and humidity of the glove box are both less than 0.1 ppm; after disassembly, it is cleaned with dimethyl carbonate and left to air dry in this environment for more than 1 hour; then a circular cutter is used to cut out a circular NCM811 positive electrode material with a diameter of 3 mm to obtain a lithium battery electrode material;

[0084] (2) The current collector of the lithium battery electrode material obtained in step (1) is fixed on a circular conductive copper sheet of the same diameter by a carbon conductive tape, and then clamped on a special sample stage for ion thinning, and placed in a processing chamber of an ion thinning instrument to perform rough processing and fine processing on the active material in sequence; wherein the process parameters for rough processing are: processing time 30 min, processing voltage 6 kV, left / right ion beam angle 4°, and rotation speed 3 r / min; the process parameters for fine processing are: processing time 60 min, processing voltage 3 kV, left / right ion beam angle 4°, and rotation speed 3 r / min.

[0085] The cross section of the lithium battery electrode material prepared in Example 1 was observed using a scanning electron microscope. Figure 2 shown.

[0086] from Figure 2 It can be seen that the cross section of the lithium battery electrode material is flat and smooth, and the cracks and morphology inside the lithium battery electrode material particles are clearly visible, which fully demonstrates that the present invention can obtain a better cross-section processing effect of the positive electrode material; the obtained high-quality cross-section SEM image will help to explore the failure mechanism of the lithium battery electrode material, and the cross-section image can be processed in combination with the artificial intelligence algorithm to further quantify the relationship between the degree of damage to the lithium battery electrode material and the battery failure. In addition, the method of the present invention significantly shortens the processing time and equipment use costs.

[0087] Example 2

[0088] The cross-section preparation method of the lithium battery electrode material is as follows:

[0089] (1) disassembling the battery, wherein the disassembly process is carried out in a glove box in an argon environment, wherein the oxygen content and humidity in the glove box are both less than 0.1 ppm; after disassembly, the battery is cleaned with dimethyl carbonate and allowed to air dry in this environment for more than 1 hour; and then a circular cutter is used to cut out a circular silicon-carbon negative electrode material with a diameter of 3 mm to obtain a lithium battery electrode material;

[0090] (2) The current collector of the lithium battery electrode material obtained in step (1) is fixed on a circular conductive copper sheet of the same diameter by a carbon conductive tape, and then clamped on a special sample stage for ion thinning, and placed in a processing chamber of an ion thinning instrument to perform rough processing and fine processing on the active material in sequence; wherein the process parameters for rough processing are: processing time 20 min, processing voltage 10 kV, left / right ion beam angle 8°, and rotation speed 3 r / min; the process parameters for fine processing are: processing time 20 min, processing voltage 6 kV, left / right ion beam angle 4°, and rotation speed 3 r / min.

[0091] The cross section of the lithium battery electrode material prepared in Example 2 was observed using a scanning electron microscope. Figure 3 shown.

[0092] from Figure 3 It can be seen that the cross section of the lithium battery electrode material is flat, smooth and clear, meeting the application requirements. By observing the cross-sectional morphology of the above silicon-carbon negative electrode material, the study of the failure mechanism of silicon-carbon negative electrode material and the optimization of negative electrode material can be effectively promoted. At the same time, it fully demonstrates that the present invention can obtain a better negative electrode material cross-sectional processing effect, significantly reducing processing time and cost.

[0093] Example 3

[0094] The cross-section preparation method of lithium battery electrode material is as follows:

[0095] A hole with a diameter of 0.1 mm is pre-opened on the current collector, and then the active material is coated on the current collector with the hole, followed by drying, and then cutting with a circular cutter to ensure that the hole is located at the center, thereby obtaining a circular NCM811 positive electrode material with a diameter of 3 mm;

[0096] The edge of the active material of the circular NCM811 positive electrode material is fixed on the conductive copper sheet by carbon conductive tape, and then clamped on the special sample stage for ion thinning, and then placed in the processing chamber of the ion thinning instrument to perform rough processing and fine processing on the opening of the collector in sequence, wherein the process parameters of the rough processing are: processing time 20min, processing voltage 10kV, left / right ion beam angle 8°, rotation speed 3r / min; the process parameters of the fine processing are: processing time 20min, processing voltage 6kV, left / right ion beam angle 4°, rotation speed 3r / min.

[0097] After the circular copper sheet was disassembled, the cross section of the lithium battery electrode material prepared in Example 3 was observed using a scanning electron microscope. Figure 4 shown.

[0098] from Figure 4 The lithium battery electrode material in the center area of ​​the view and its cross-section processing effect can be clearly observed, and a large range of lithium battery electrode material cross-section preparation is obtained, while the surface is flat and the cross-section is clear, which can meet the needs of actual observation. This shows that the present invention has a variety of applications in the preparation of lithium battery electrode material cross-sections.

[0099] Comparative Example 1

[0100] The preparation method of metallographic grinding and polishing is:

[0101] The NCM811 cathode material samples were prepared using cold mounting resin and then subjected to a series of mechanical grinding and polishing.

[0102] The cross section of the lithium battery electrode material prepared in Comparative Example 1 was observed using a scanning electron microscope. Figure 5 shown.

[0103] from Figure 5 It can be seen that the cross-sectional flatness of the lithium battery electrode material obtained by the metallographic grinding and polishing method is poor, and it is difficult to observe the internal morphology and structure of the material. In summary, considering that metallographic grinding and polishing are limited by grinding and polishing reagents, processing proficiency, and sample preparation time, the use of metallographic grinding and polishing to prepare lithium battery electrode material samples is relatively cumbersome and the effect is average.

[0104] Comparative Example 2

[0105] The NCM811 cathode material particles were cut using FIB cutting.

[0106] The cross section of the lithium battery electrode material prepared in Comparative Example 2 was observed using a scanning electron microscope. Figure 6 shown.

[0107] from Figure 6 It can be seen that there are obvious traces of ion beam processing on the particle cross section.

[0108] From the above examples and comparative examples, it can be seen that the method for preparing the cross section of a lithium battery electrode material provided by the present invention can meet the requirements of preparing electrode sample materials for in-situ and ex-situ observations, and can provide good cross-sectional flatness of the lithium battery electrode material. The present invention applies an ion thinning instrument to the preparation of cross-sectional samples of electrode materials, expanding the application field of the device.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A multi-purpose and low-cost method for preparing a cross-section of a lithium battery electrode material, comprising: The current collector of the lithium battery electrode material is fixed on the conductive copper sheet, and then the active material of the lithium battery electrode material is polished by argon ion beam; Alternatively: fixing the active material of the lithium battery electrode material on a conductive copper sheet, then performing argon ion beam polishing on the current collector of the lithium battery electrode material until the active material is exposed, and then performing argon ion beam polishing on the exposed active material; Alternatively: coating the open-pore current collector with an active material to obtain a lithium battery electrode material; Fixing the active material of the lithium battery electrode material on a conductive copper sheet, and then performing argon ion beam polishing on the active material at the opening of the current collector; The argon ion beam polishing includes rough machining and fine machining performed sequentially; The parameters of the rough machining include: machining time 20 to 30 min, voltage 6 to 10 kV and ion beam angle 3 to 10°; The parameters of the finishing process include: processing time 30 to 90 min, voltage 3 to 6 kV and ion beam angle 3 to 10°; The voltage for rough machining is higher than the voltage for fine machining.

2. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: The lithium battery electrode material is a ternary polycrystalline positive electrode material, a ternary single crystal positive electrode material or a silicon-carbon negative electrode material.

3. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: The obtaining of the lithium battery electrode material includes disassembling the battery.

4. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: The types of batteries in the disassembled batteries include button batteries, cylindrical batteries or soft-pack batteries.

5. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: The argon ion beam polishing is performed in an ion thinning instrument.

6. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: The rotation speed of the lithium battery electrode material during the argon ion beam polishing is 3 r / min.

7. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: The parameters of the rough machining include: machining time of 20 to 30 minutes, voltage of 8 to 10 kV and ion beam angle of 3 to 8 degrees.

8. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: The parameters of the fine machining include: machining time of 60 to 90 minutes, voltage of 3 to 6 kV and ion beam angle of 3 to 4 degrees.

9. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: When the lithium battery electrode material is LiNi 0.8 Co 0.1 Mn 0.1 When O2 positive electrode material is used, the rough machining time is 30 minutes, the voltage is 6 kV, the ion beam angle is 3 to 4 degrees, and the rotation speed is 3 r / min; the fine machining time is 60 to 90 minutes, the voltage is 3 kV, the ion beam angle is 3 to 4 degrees, and the rotation speed is 3 r / min.

10. The method for preparing a cross section of a lithium battery electrode material according to claim 1, characterized in that: When the lithium battery electrode material is a silicon-carbon negative electrode material, the rough machining time is 20 min, the voltage is 10 kV, the ion beam angle is 8°, and the rotation speed is 3 r / min; the fine machining time is 20 min, the voltage is 6 kV, the ion beam angle is 4°, and the rotation speed is 3 r / min.